Immotile Short-Tail Sperm Defect in Nelore (Bos taurus indicus) Breed Bulls - Siqueira, J. B. [UNESP]; Pinho, R. O.; Guimaraes, S.; Miranda-Neto, T.; Guimaraes, J. D. (Wiley-Blackwell Publishing, Inc, 2010)
ContentThis case study reported the presence of short tail sperm defect in the semen of three Nelore breed bulls. The sperm presented 0% of motility in the three animals evaluated and a total of 70%, 61% and 34% of pathologies of the intermediate piece of the tail respectively for animals 1, 2 and 3. It was identified that animals 2 and 3 had high degree of inbreeding, although no relationship was found with animal 1. Animal 2 was the only one that presented inbreeding coefficient (6.25%). His half-sib (animal 3) and animal 1, from the same herd, had shown no inbreeding, showing that inheritance is not the only determinant factor for its incidence on Nelore males.